Preparing leaders for the multi-generational workforce. Issue 3 (8th August 2016) - Dwyer, Rocky J; Azevedo, Ana
Abstract : Purpose: This paper advocates the need for educational leadership to understand and consider the immediate role and challenges associated with the unique values and characteristics of an age-diverse population and their impact on teaching and the facilitation of learning. Design/methodology/approach: The paper draws on the review of the generational and diversity literatures and related organizational best practices to identify key definitions and empirical findings and to develop recommendations which can be deployed in future research and practice in different types of organizational settings. Findings: This paper provides insights into how organizational leaders can promote a multicultural environment that leverages multi-generational differences. Also, the present study offers innovative pedagogical approaches that can help better prepare future business leaders for these challenges. Research limitations/implications: The study attempts to reignite the debate through a detailed review that describes the current understanding of generational differences amongst four generational cohorts. Given the research approach, the recommendations may lack generalizability. Practical implications: This paper advocates the need to understand generational differences in order to manage the challenges associated with differences in attitudes, values and preferences regarding leadership, Human Resource practices and organizational change initiatives. Originality/value: This paper enhances knowledge and understanding at the theoretical and practical levels enabling business leaders and faculty to gain insight regarding the generational differences and unique characteristics of four organizational workgroups – Veterans, Baby Boomers, Generation X and Generation Y.